OSTEONECROSE INDUZIDA POR GLICOCORTICOIDES EM PACIENTES COM LÚPUS ERITEMATOSO SISTÊMICO: UMA REVISÃO SISTEMÁTICA (Movimenta (ISSN 1984-4298), 2022)
ABSTRACTObjective: to clarify the relationship of glucocorticoid-induced osteonecrosis (ON) in patients with systemic lupus erythematosus (SLE) and to verify if there is a dose x duration relationship, using the systematic review method. Methods: A systematic literature search was performed on PubMed, LILACS, SciELO and Cochrane Library. This search prioritized studies published between the years 2009-2019, which involved the use of glucocorticoids as a form of treatment for SLE and which had the presence of ON as an outcome. Results: From 1,051 articles previously identified in the databases, 6 studies were selected that met the criteria established for this systematic review. The articles indicated a great tendency for the presence of NO in patients using corticosteroids, demonstrating that higher doses tend to increase the chance of this manifestation. The age of earlier diagnosis of SLE showed a greater relationship with the onset of ON, manifesting mainly in the hip joint. Conclusion: Although most studies point to the relationship of corticosteroid therapy with regard to dose and time with the onset of ON, a greater number of studies need to be evaluated, since some of our findings demonstrate this manifestation with doses equivalent to 7.5mg/day, while another found the possibility of this unfolding being typical of the course of the disease.KEYWORDS: systemic lupus erythematosus; osteonecrosis; glucocorticoids
Keywords: systemic lupus erythematosus; osteonecrosis; glucocorticoids